NEOLIBERALISM AND SUBJECTIVITY: THE PSYCHOTHERAPEUTIC CLINIC IN THE FACE OF THE 6X1 WORK SCHEDULE (PRÁXIS EM SAÚDE, 2025)
This extended abstract aims to analyze the relationship between the 6x1 work schedule, psychological distress, and clinical psychological practice under a neoliberal framework. It is a qualitative literature review with an exploratory and analytical approach, carried out between 2012 and 2023 in the Scielo and CAPES Portal scientific databases. The findings show that, although discussions on workers’ psychological distress are raised, no studies were found that directly associate the work schedule with the therapeutic clinical context. From the analysis, it is observed that neoliberalism contributes to the construction of subjectivity, being able to naturalize precarious conditions that generate different forms of suffering. It can be concluded that, in order to achieve an expanded clinical psychology, it is necessary to integrate the socio-historical perspective into the process of understanding how an exhaustive work schedule impacts the individual. In this way, the aim is to promote professional practices that do not reinforce the productivist logic but instead enable social transformation.
Keywords: Work; Neoliberalism; Psychology